PENGARUH BELANJA MODAL DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN KINERJA KEUANGAN DAERAH DENGAN PENDAPATAN ASLI DAERAH SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Kabupaten dan Kota di Provinsi Jawa Tengah Tahun 2014-2016) - Anisa Munasifah, 14.05.52.0193; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
The research aims to examine the effect of Capital Expenditure and Balancing Fund on Financial Performance Growth with Local Original Income as intervening variable. Population in this research is all Regency and City in the Central Java Province. The data used are secondary data derived from Report on Realization of Regional Revenue and Expenditure Budget of Central Java Province in 2014- 2016. The sampling method was conducted using census method. The analytical methods used are descriptive statistics, classical assumption test, multiple linear regression, and path analysis. The result of this research is Capital Expenditure and Balancing Fund havepositive and significant influence to the Original Revenue, Local Revenue have a positive and significant impact to financial performance growth (financing capability ratio), Local Revenue has a positive and insignificant effect on the growth of financial performance (expenditure efficiency ratio), Capital Expenditure directly influence against the growth of financial performance, but indirectly capital expenditure through the original revenue does not affect the growth of financial performance (financing capability ratio), then Capital Expenditure can influence directly or indirectly to the Growth of Financial Performance (the ratio of the efficiency of budgetary expenditure) through the Local Revenue, the Balance Fund can directly and indirectly affect the Financial Performance Growth (the ratio of financing capability and the ratio of the efficiency of budget expenditure) through the Original Revenue.Keywords: Capital Expenditure, Balancing Fund, Local Original Income and Local Financial Performance